Does health literacy influence health-related lifestyle behaviors among specialists of health management? A cross-sectional study - Shunsuke Kinoshita; Nobutaka Hirooka; Takeru Kusano; Kohei Saito; Ryutaro Aoyagi (BMC Primary Care, 2024)
Abstract Background Noncommunicable diseases (NCDs), such as health-related lifestyle diseases, are the leading cause of mortality and societal and economic burdens. Poor lifestyle behaviors, which are modifiable to improve health, can cause diseases, including NCDs. Health literacy has been recognized as an important determinant of health, and studies have shown that higher health literacy is associated with better health outcomes and positive health-related behaviors. However, few studies have investigated the association between health literacy and health-related lifestyle behaviors to understand the mechanistic link between them. Thus, this study investigated the extent to which health literacy at different levels influences health-related lifestyle behaviors. Methods A cross-sectional study was conducted among Japanese health management specialists (N = 1,920). Functional, critical, and communicative health literacy were measured. Lifestyle behaviors (exercise, diet and nutrition, sleep, rest, smoking, and alcohol intake), in line with the Japanese National Health Promotion Program, were assessed and calculated into a total cumulative score of health-related lifestyle behaviors. Moreover, we analyzed the associations between the three levels of health literacy and lifestyle behaviors using regression analyses by adjusting for socio-psycho-demographic factors. Results Multiple linear regression analyses showed a significant association between the Japanese version of the European Health Literacy Survey Questionnaire and total health-related lifestyle scores (standardized β = 0.160, p < 0.001, R 2 = 0.136) after adjusting for sociodemographic factors. Similarly, the association between communicative and critical health literacy and the total health-related lifestyle scores was significant (standardized β = 0.122, p < 0.001, R 2 = 0.125). The analysis indicated that individuals who had higher level of health literacy (critical and communicative) than functional health literacy (Japanese version of the Newest Vital Sign score) had higher health-related lifestyle behaviors. Conclusions A higher level of health literacy is associated with health-related lifestyle behaviors. Health literacy can be a target for interventions to achieve the national goal of lifestyle-related disease prevention and control.